Enhanced spontaneous polarization in double perovskite Bi2FeCrO6 films. Issue 9 (4th March 2019) - Meng, Dehuan; Xiao, Yunsheng; He, Hongcai; Liao, Yulong; Zhang, Huaiwu; Zhai, Junyi; Chen, Zuhuang; Martin, Lane W.; Bai, Feiming
Abstract: We report the pulsed‐laser deposition of epitaxial double‐perovskite Bi2 FeCrO6 (BFCO) films on the (001)‐, (110), and (111)‐oriented single‐crystal SrTiO3 substrates. All of the BFCO films with various orientations show the 1 / 2 1 / 2 1 / 2 and 3 / 2 3 / 2 3 / 2 superlattice‐diffraction peaks. The intensity ratios between the 1 / 2 1 / 2 1 / 2 ‐superlattice and the main 111‐diffraction peak can be tailored by simply adjusting the laser repetition rate and substrate temperature, reaching up to 4.4%. However, both optical absorption spectra and magnetic measurements evidence that the strong superlattice peaks are not correlated with the B ‐site Fe 3+ /Cr 3+ cation ordering. Instead, the epitaxial (111)‐oriented Bi2 FeCrO6 films show an enhanced remanent polarization of 92 μC/cm 2 at 10 K, much larger than the predicted values by density‐functional theory calculations. Positive‐up‐negative‐down (PUND) measurements with a time interval of 10 μs further support these observations. Therefore, our experimental results reveal that the strong superlattice peaks may come from A ‐ or B ‐site cation shifts along the pseudo‐cubic [111] direction, which further enhance the ferroelectric polarization of the BFCO thin films.